Norwegian Garden Cities Yesterday, Today - and Tomorrow? - Smith Wergeland, Even (Libelli: Minimono, 2022)
This book deals with the legacy of Norway's garden cities. It tracks the origins of the Norwegian garden city movement and discusses the current status of built examples. Through a detailed study of one example, Sinsen Garden City in Oslo, the book links the garden city heritage to a number of ongoing scholarly debates on topics like densification, sustainability, socio-economic conditions, life quality and neighborhood satisfaction. While the garden city can be criticized for its association with sprawl and its failure to deliver affordable housing for all, it has gained new momentum as a green, resilient resource in light of theoretical platforms like garden ecology and circular heritage. A key argument in the book is that the garden city is a pioneering example of a serious commitment to the environmental cause through architecture and planning. It is a reminder of the importance of environmental awareness today, not least because it accentuates the climate crisis through changing conditions for gardening in the summer and skiing in the winter. A garden city may have its faults and inadequacies, especially in regard to housing prices and social exclusion, but the overall conclusion is that it represents a valuable legacy with endurable qualities that cities will be needing in the future too.